The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph192214985
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Cardiometabolic Risk Factors in the Mixed Hypercholesterolemic Populations with Respect to Gender, Age, and Obesity in Asir, Saudi Arabia

Abstract: This record study aimed to investigate the prevalence of metabolic syndrome (MetS) profiles regarding sex, age, and obesity for the riskier factor of cardiovascular diseases in a general population in Saudi Arabia. Laboratory and anthropometric measurements were performed on non-specific participants with variant ages and BMI in either sex. Serobiochemical changes were measured for metabolic profiles, i.e., A1C/FSG, TC, TGC, HDLC/LDLC, Vit.D, TSH/T4, Hb, and Cr. The study was applied in a Polyclinic, Abha, Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Most of the studies which investigated CVD and risk factors in women in Saudi Arabia were either small cross-sectional studies targeting young college students [ 8 , 9 , 10 ], mostly investigating one risk factor for CVD [ 11 , 12 ], or studies which included both men and women but did not include analysis to investigate the influence of age, or the hormonal changes of pregnancy and the menopause on the CVD risk factors [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies which investigated CVD and risk factors in women in Saudi Arabia were either small cross-sectional studies targeting young college students [ 8 , 9 , 10 ], mostly investigating one risk factor for CVD [ 11 , 12 ], or studies which included both men and women but did not include analysis to investigate the influence of age, or the hormonal changes of pregnancy and the menopause on the CVD risk factors [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study of the MetS and cardiometabolic risk factors was conducted in KSA that included 648 participants from the “general population” who visited the Specialized Polyclinic of Abha, Asir, KSA [ 44 ]. The patients had high rates of the features of MetS: 69.4% diabetes and 92.2% obesity.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Among them, two were cross-sectional studies in Riyadh city, conducted on patients in primary healthcare centers, and conducted in primary healthcare centers and universities and online [7,21]. There was a prospective urban rural epidemiology study that compared rural and urban areas and found more physical inactivity-related risks in rural areas [24]; one included Hail City residents [30], one was a cross-sectional study including the general population in Abba [27], two were systematic literature reviews [25,26], one was conducted among nurses [28], and one was conducted during COVID-19 quarantine among medical students at Tabuk University [22]. Physical inactivity or low physical activity was reported in up to 69.4% of the population, mostly among Saudi women, with up to 1.5 odds of CVD [24].…”
Section: Physical Inactivity/sedentary Lifementioning
confidence: 99%
“…It also found a negative correlation between Mediterranean diet and low-density lipoprotein (LDL) levels, a risk factor for CVD [19]. A study exploring metabolic syndrome and cardiometabolic risk factors established that unhealthy junk food consumption increased risks for metabolic syndrome, increased serum cholesterol, and eventually higher exposure to CVD [27]. Similarly, five studies (three cross-sectional and two cohorts) reported that high cholesterol levels were associated with high risks of CVD [14,18,29,31,32].…”
Section: Unhealthy Dietmentioning
confidence: 99%